Inhibition of Ultraviolet B-induced Apoptosis in Fibroblasts by Human Umbilical Cord Blood Mesenchymal Stem Cell Conditioned Media via the Phosphatidylinositol-3-Kinase/Akt Pathway - Ferry Sandra; Dian Andriani Ratna Dewi; I Nyoman Mantik Astawa; Wimpie Pangkahila; Angliana Chouw; Maria Celinna; Nurrani Mustika Dewi (Iranian Journal of Medical Sciences)
Background: Ultraviolet B (UVB) irradiation induces photoaging and apoptosis in various cell types. Inhibition of UVB-induced apoptotic pathways has been explored in different apoptotic cascades. Conditioned media from human umbilical cord blood mesenchymal stem cells (CM-hUCB-MSC) contain important substances for cell regeneration. However, the potential of CM-hUCB-MSC in preventing UVB-induced apoptosis has not been clearly elucidated. Therefore, the current research was conducted to investigate the potential of CM-hUCB-MSC in inhibiting UVB-induced apoptosis and its role in the antiapoptotic signaling pathway.Methods: An experimental in vitro study was conducted at PT. Prodia StemCell Indonesia, Jakarta, Indonesia, 2019-2022. Initially, hUCB-MSCs were isolated and cultured to produce CM-hUCB-MSC. NIH3T3 cells were pretreated with/without 50 μM LY294002, treated with/without 10% CM-hUCB-MSC, and then irradiated with/without UVB. Subsequently, the cells were analyzed using sub-G1, immunofluorescence, and immunoblotting assays. One-way analysis of variance (ANOVA) was used for data analysis, followed by Tukey’s honest significant difference (HSD) test or the Kruskal-Wallis test, followed by the Dunn-Bonferroni test using IBM SPSS Statistics software version 21. Statistical significance was determined at P<0.05.Results: CM-hUCB-MSC significantly inhibited UVB-induced apoptosis in NIH3T3 cells (P=0.002, Dunn-Bonferroni test). CM-hUCB-MSC significantly induced Akt phosphorylation at Ser 473 in UVB-irradiated NIH3T3 cells (P<0.001, Tukey’s HSD test). The CM-hUCB-MSC-induced phosphorylation of Akt was significantly inhibited by LY294002 (P<0.001, Tukey’s HSD test).Conclusion: Taken together, it can be concluded that CM-hUCB-MSC inhibits UVB-induced NIH3T3 cell apoptosis via the activation of phosphatidylinositol-3-kinase (PI3K)/Akt signaling cascades.